Brain histopathological study and prognosis in MOG antibody‐associated demyelinating pseudotumor. Issue 2 (8th January 2019) - Shu, Yaqing; Long, Youming; Wang, Shisi; Hu, Wanming; Zhou, Jian; Xu, Huiming; Chen, Chen; Ou, Yangmei; Lu, Zhengqi; Lau, Alexander Y.; Yu, Xinhua; Kermode, Allan G.; et al.
Abstract: Our objective was to examine the brain biopsies by histopathology and investigate the prognosis of patients with myelin oligodendrocyte glycoprotein antibody‐associated demyelinating pseudotumor. The clinical, MRI, and histological features of two patients with myelin oligodendrocyte glycoprotein antibody‐associated demyelinating pseudotumor were reviewed. Both patients were treated with steroid plus rituximab and followed up. The brain biopsies of both cases revealed T cells, macrophages, and complement‐mediated demyelination, which was in accord with multiple sclerosis‐like pathology. Moreover, both cases showed favorable response to steroid plus rituximab therapy. Our cases add a new variant to the myelin oligodendrocyte glycoprotein‐encephalomyelitis spectrum, which favorably responds to immunotherapy.